Mengukur Kinerja Pasar Melalui Elemen Inovasi pada UKM Sektor Makanan dan Minuman di Kota Padang - Alvi Syukri Faisal; M. Ma'ruf; Ratni Prima Lita; Tedi Hidayat (Jurnal Manajemen dan Kewirausahaan, 2021)
In Small and Medium Enterprises (SMEs), especially in the food and beverage sector, process innovation is an important construct that can maintain the sustainability of product innovation and improve marketing innovation strategies for optimal market performance. This study aims to examine the effect of innovation elements, namely product, process, and marketing on the market performance of SMEs in the food and beverage sector, and the effect of marketing innovation on market performance when mediated by product innovation. Using a purposive sampling technique with the criteria of SMEs in the food and beverage sector that is not a franchise. A total of 104 feedback questionnaires was analyzed using the SmartPLS 3.3 software and Microsoft Excel. This study found that all hypotheses were supported significantly in a positive relationship.